Collection management of electronic resources in engineering college libraries of Aligarh, India: a study. (28th January 2020) - , Muzamil Mushtaq; , Ariba Tausif
Abstract : Purpose: The purpose of this paper is to analyze the e-resource collection development practices of the engineering college libraries of Aligarh. The research includes budgeting, collection development policy, collection evaluation, sources of funds, modes of procurement, pricing models and other aspects related to collection development activity. Design/methodology/approach: The descriptive method was used for conducting the study, in which a well-structured questionnaire was administered followed by interview of the librarians of six engineering college libraries under study. Findings: It was found that these colleges are much more interested in focusing on building a strong e-resource collection in their libraries. During the past few years, the budget has also been increased in majority of libraries for the acquisition of e-resources. The study found that the major factors affecting the selection of electronic resources (e-resources) in these colleges are quality, subject coverage, license agreement and vendor support. It was also revealed that majority of libraries lack proper collection development policy, especially for e-resources. The study suggested that these libraries should build their collections keeping in mind the different areas of specializations of engineering studies and the contemporary changes in the field. Research limitations/implications: The paper is restricted exclusively to the study of collection development process of e-resources and the librarians of six major engineering colleges of Aligarh as respondents. Practical implications: This study has great importance for the librarians of the similar engineering colleges in India. The findings and suggestions of the study can help not only in understanding the engineering college librarianship and its current trends but can also help library professionals who are facing similar challenges in their libraries. Originality/value: The present study is about the e-resource collection development practices followed in engineering colleges of Aligarh, which can serve as a pedestal for future studies in other academic and special libraries in India and elsewhere.